Mass Production of Lemna minor and Its Amino Acid and Fatty Acid Profiles - Chakrabarti, Rina; Clark, William D.; Sharma, Jai Gopal; Goswami, Ravi Kumar; Shrivastav, Avanish Kumar; Tocher, Douglas R. (Frontiers in Chemistry, 2018)
The surface floating duckweed Lemna minor (Lemnaceae) is a potential ingredient to replace the application of fish-meal in the aqua-feed. The culture technique of the duckweed was standardized in outdoor tanks and then applied in the pond. Three consecutive experiments were conducted in tanks (1.2 m x 0.35 m x 0.3 m). In experiment 1, four different manures were used. In manure 1 (organic manure, OM) and manure 3 (2x OM), cattle manure, poultry droppings and mustard oil cake (1:1:1) were used; in manure 2 (inorganic fertilizer, IF), urea, potash, triple superphosphate were used; manure 4 (2x OM+IF) was a combination of manure 2 and manure 3. In experiment 2, manure 1 (OM) and manure 2 (IF) were used and manure 3 (OM+IF) was a combination of both manures. In experiment 3, OM and IF were selected. In pond (20 m x 10 m x 0.5 m), OM was applied. Fresh duckweed was seeded after 5 days of manure application. In experiments 1 and 3, total production was significantly (P < 0.05) higher in OM compared to other treatments. In experiment 2, there was no significant (P < 0.05) difference in production between OM and IF. In pond, relative growth rate of duckweed ranged from 0.422 - 0.073 g/g/day and total production was 702.5 Kg/ha/month (dry weight). Protein, lipid and ash contents were higher in duckweed cultured in OM compared to IF. The duckweed was a rich source of essential (39.20%), non-essential (53.64%) and non-proteinogenic (7.13%) amino acids. Among essential amino acids, leucine, isoleucine and valine constituted 48.67%. Glutamic acid was 25.87% of total non-essential amino acids. Citrulline, hydroxiproline, taurine etc. were found in the duckweed. The fatty acid composition was dominated by PUFA, 60-63% of total fatty acids, largely -linolenic acid (LNA, 18:3n-3) at around 41 - 47% and linoleic acid (LA, 18:2n-6) at 17 - 18%. The nutritional value of duckweeds and their production potential in the pond conditions were evaluated. Duckweed biomass may thus be used to replace commercial fish-meal that is currently used in aquaculture.